Yanghe Pingchuan Granules Alleviate Airway Inflammation in Bronchial Asthma and Inhibit Pyroptosis by Blocking the TLR4/NF-κB/NRLP3 Signaling Pathway - Lingyu Pan; Yan Chen; Yeke Jiang; Yehong Sun; Yanquan Han; Yongzhong Wang (Mediators of Inflammation)
Bronchial asthma (BA) is a chronic inflammatory disease of the airway. Previous research has shown that Yanghe Pingchuan granules (YPGs) exert a precise therapeutic effect on BA. In our previous work, we showed that YPGs improved inflammation of the airways in rat models of BA. Other studies have shown that the pathogenesis of BA is closely related to pyroptosis and that the TOLL-like receptor pathway plays a key role in the mediation of pyroptosis. Therefore, in the present study, we established a rat model of BA by applying the concept of pyroptosis and used the TLR4/NF-κB/NRLP3 signaling pathway as the target and YPGs as the treatment method. We evaluated the effects of YPGs on airway inflammation and pyroptosis in the model rats by HE staining, Masson’s staining, AP-PAS staining, western blotting, and real-time quantitative PCR. The results showed that Yanghe Pingchuan granules could significantly improve the inflammatory response of bronchial tissue in BA rats, reduce the content of inflammatory factors IL-1β and IL-18, and inhibit the expression of pyroptosis factor. Meanwhile, YPG can block the TLR4/NF-κB signaling pathway. These findings suggest that YPG may be an effective drug for the treatment of BA by blocking the TLR4/NF-κB signaling pathway and inhibiting pyroptosis.